Erratum: Exploring Profitability of Compost Micro Enterprises in Chimaltenango, Guatemala: A Case Study of Business Sustainability for International Development - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Silberg, T., Murphrey, T. P., Wingenbach, G., & Lombardini, L. (2013). Exploring Profitability of Compost Micro Enterprises in Chimaltenango, Guatemala: A Case Study of Business Sustainability for International Development. Journal of International Agricultural and Extension Education, 20(3), 58-70” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1437